Development of Learning Media for Introductory Information and Communication Technology Courses - Mustapa, Mahmud; Ummiati Rahmah; Muh. Asjart (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
This research aims to (1) assess the current learning conditions in the